Synthesis and biological evaluation of a series of fatty acid amides from Echinacea. Issue 16 (15th August 2015) - Moazami, Yasamin; Gulledge, Travis V.; Laster, Scott M.; Pierce, Joshua G.
Graphical abstract: Abstract: Alkylamides are lipophilic constituents of Echinacea and possess numerous biological activities. Although significant effort has been focused on the study of crude Echinacea extracts, very little is known regarding the activities of the individual constituents that make up these herbal treatments. Herein we explore the SAR of simple alkylamides found in Echinacea extracts with respect to their ability to decrease the production of the pro-inflammatory mediator TNF-α. Our results have revealed the key structural requirements for activity and provide lead compounds for further investigation of these poorly understood molecules.